Genetic improvement through induced mutation in dahlia (Dahlia variabilis Desf.) - Manu R (Department of Plant Breeding and Genetics, College of Agriculture, 2017)
The per cent sprouting and survival at 15 days (%) decreased with increase in dose of gamma rays which was exhibited by all the three varieties in the same fashion. The reduction at higher doses might be attributed to genetic loss due to chromosomal aberrations and gene mutation which might be lethal for sprouting and survival. A gradual decrease in plant height was recorded with increase in dose of gamma rays which was evident in data recorded at 30, 60, 90 and 120 days after planting. Reduction in vegetative growth after exposure to radiations might be due to interference in normal mitosis and frequent occurrence of mitotic aberrations, inhibition of rate of assimilation and also due to changes in auxin level or due to inactivation of auxin.